2014
DOI: 10.1177/1556264614540592
|View full text |Cite
|
Sign up to set email alerts
|

Trial Participants’ Understanding of Randomization, Double-Blinding, and Placebo Use in Low Literacy Populations

Abstract: Concerns have been raised about the limits of understanding of consent by clinical trial participants in developing countries. Consequently, this empirical study was conducted in Malawi to assess microbicide trial participants' understanding of randomization, double-blinding, and placebo use. The study used a combination of quantitative and qualitative methods, including structured questionnaire interviews with a random sample of 203 individual participants, four in-depth interviews with research nurses, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Previous studies have explored adults’ awareness of some of the key concepts involved in health claim appraisal – for example, randomization, double‐blinding and informed consent . Some studies have explored university health students’ and health professionals’ understanding of these concepts – typically as part of evidence‐based practice .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have explored adults’ awareness of some of the key concepts involved in health claim appraisal – for example, randomization, double‐blinding and informed consent . Some studies have explored university health students’ and health professionals’ understanding of these concepts – typically as part of evidence‐based practice .…”
Section: Introductionmentioning
confidence: 99%
“…Those with lower education levels are less able to answer questions correctly. For all subjects, there are key research concepts such as randomization and placebo that are hard to understand (Ndebele et al 2014). While some suggest approaches to simplifying the language used in consent forms and attending to the format in which the information is presented, others suggest that the best way to help subjects understand is to provide potential research subjects the opportunity to discuss their decision to enroll with someone other than the principal investigator (Naanyu, Some, and Siika 2014).…”
Section: Barriers and Facilitators To The Consent Process In A Study mentioning
confidence: 99%
“…It has also been shown that low-income and minority women overwhelming prefer (97%) the opportunity to discuss the consent form with a member of the study team when compared to reading the form on their own (Jallo et al 2013). And relatedly, it has been recommended that those tasked with reviewing the consent form with the potential subject be adequately trained, and preferably be a member of that cultural community (Ndebele et al 2014). One way to assure that potential subjects understand the information conveyed is to administer a quiz of understanding (Shafiq and Malhotra 2011).…”
Section: Barriers and Facilitators To The Consent Process In A Study mentioning
confidence: 99%
“…[40][41][42] In addition, studies of language in trials have demonstrated 'that there is a difference between understanding the mechanics of a process, such as randomisation (how it occurs), and participants' comprehension of the purpose of that process (why it is necessary and its implications). 41,43 It is argued that both are required for informed consent and recall of one might hide misapprehension of the other'. 34 In the case of Deaf people's understanding of key trial-related terminology, the situation is more complex.…”
Section: Introductionmentioning
confidence: 99%